2021
DOI: 10.3390/plants10102195
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Insect Assemblage and Associated Floral Volatiles of Black Cherry (Prunus serotina)

Abstract: Black cherry is an ecologically important high-value wood. A decline of its regeneration has been reported in the USA, which could be associated with a lack of pollination. This study was conducted to identify insects visiting black cherry flowers, to determine whether insects captured on the flowers carry black cherry pollen and to identify the volatile organic compounds (VOCs) emitted by flowers of black cherry. A two-year insect survey was conducted before, during and after the black cherry bloom. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…Our study also revealed that the canopy traps captured significantly more insects (~60% of all insects captured in this study) than the ground traps ( Table 1 , Figure 3 ). In line with our previous study [ 12 ] two specific insect orders (i.e., Lepidoptera and Thysanoptera) were found to be significantly more abundant in the canopy of black cherry, indicating that these insects might be utilizing flowers and thus contributing to the pollination of black cherry. Likewise, the number of Diptera captured in the canopy of black cherry trees was higher than that on the ground ( Table 1 ), however, in contrast to our previous study [ 12 ], the difference in Diptera captured in the two trap positions was not significant ( p = 0.123) in the current study ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study also revealed that the canopy traps captured significantly more insects (~60% of all insects captured in this study) than the ground traps ( Table 1 , Figure 3 ). In line with our previous study [ 12 ] two specific insect orders (i.e., Lepidoptera and Thysanoptera) were found to be significantly more abundant in the canopy of black cherry, indicating that these insects might be utilizing flowers and thus contributing to the pollination of black cherry. Likewise, the number of Diptera captured in the canopy of black cherry trees was higher than that on the ground ( Table 1 ), however, in contrast to our previous study [ 12 ], the difference in Diptera captured in the two trap positions was not significant ( p = 0.123) in the current study ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with our previous study [ 12 ] two specific insect orders (i.e., Lepidoptera and Thysanoptera) were found to be significantly more abundant in the canopy of black cherry, indicating that these insects might be utilizing flowers and thus contributing to the pollination of black cherry. Likewise, the number of Diptera captured in the canopy of black cherry trees was higher than that on the ground ( Table 1 ), however, in contrast to our previous study [ 12 ], the difference in Diptera captured in the two trap positions was not significant ( p = 0.123) in the current study ( Figure 3 ). Remarkably, the species diversity of all the insect species and that of Diptera in the removal treatment were significantly higher in the ground traps than in canopy traps ( Figure 5 ), suggesting that the resources (i.e., nectar and pollen) in the removal stands were less abundant in the canopy than on the ground.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations